2005
DOI: 10.1183/09031936.05.00045004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of treating severe nasal obstruction on the severity of obstructive sleep apnoea

Abstract: An association between mouth breathing during sleep and increased propensity for upper airway collapse is well documented, but the effect of treatment for nasal obstruction on mouth breathing during sleep and simultaneous obstructive sleep apnoea (OSA) severity has not been described previously.A randomised single blind placebo-and sham-controlled crossover study of treatment (topical decongestant and external dilator strip) for nasal obstruction was carried out in 10 patients (nine males; mean¡SEM 46¡5 yrs) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
81
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(89 citation statements)
references
References 40 publications
3
81
0
3
Order By: Relevance
“…Mouth breathing during the growth phase is an important factor responsible for a sequence of events that commonly result in growth changes and abnormalities of cranial and maxillomandibular development 14 . An association between mouth breathing during sleep and increased propensity for upper airway collapse has been well documented 20 . Moreover, there seems to be a correlation between the anatomical shape of the upper airways and abnormalities in craniofacial morphology among mouth breathing individuals 21 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mouth breathing during the growth phase is an important factor responsible for a sequence of events that commonly result in growth changes and abnormalities of cranial and maxillomandibular development 14 . An association between mouth breathing during sleep and increased propensity for upper airway collapse has been well documented 20 . Moreover, there seems to be a correlation between the anatomical shape of the upper airways and abnormalities in craniofacial morphology among mouth breathing individuals 21 .…”
mentioning
confidence: 99%
“…Children with abnormal craniofacial patterns show a predisposition towards some types of respiratory sleep disorder, as do children with tonsillar and adenoid hypertrophy. These factors favor the development of mouth breathing 10,20 . Mouth breathing during the growth phase is an important factor responsible for a sequence of events that commonly result in growth changes and abnormalities of cranial and maxillomandibular development 14 .…”
mentioning
confidence: 99%
“…Mouth opening is associated with increased upper airway collapsibility during sleep. 1 It has been reported that upper airway collapsibility and resistance during sleep were significantly higher in subjects who were breathing through the mouth than in those who were breathing through the nose, which is different from that seen during the conscious state. 2,3 Other reasons for nasal breathing over mouth breathing during normal sleep are based on the physiological effects of decreased nasal airflow.…”
Section: Of Patterns the Nasal Airway And Sdbmentioning
confidence: 40%
“…However, in nasal diseases such as nasal deviation or inferior turbinate hypertrophy, nasal obstruction can be bypassed by opening the mouth and allowing a greater volume of air to be inspired and expired. McLean et al 1 showed that oral breathing during sleep is induced by increased nasal resistance. Mouth opening increased upper airway collapsibility during sleep, which is different from that seen when awake.…”
mentioning
confidence: 99%
“…CPAP can worsen the congestion and exacerbate the problem. 18 Increased nasal resistance may lead to mouth opening and oral breathing, 19 which are associated with a significantly higher upper airway resistance than nasal breathing. 20 Oral breathing may also be associated with higher air leak, which itself has been linked to lower CPAP adherence.…”
mentioning
confidence: 99%